Lactobacillus reuteri strain 8008 attenuated the aggravation of depressive-like behavior induced by CUMS in high-fat diet-fed mice through regulating the gut microbiota - Canye Li; Zuanjun Su; Zhicong Chen; Jinming Cao; Xiufeng Liu; Feng Xu; Feng Xu (Frontiers in Pharmacology, 2023)
Objective: Gut microbiota play a key role in the pathogenesis of obesity and depression. Probiotics are a preventive strategy for obesity and a novel treatment for depression symptoms. However, the ameliorative or therapeutic effect of potential probiotic candidate Lactobacillus reuteri (L. reuteri) on obesity and depression comorbidity still remains unclear. We investigated the effects of chronic unpredictable mild stress (CUMS) in high-fat diet-fed mice and the effects of Lactobacillus reuteri strain 8008 on various disease indicators of obesity and depression comorbidity disease.Methods: Forty male C57BL/6 mice were randomized into 2 groups: the normal control (NC) group (n = 10) and the high-fat diet (HFD) group (n = 30), being fed with normal diet (ND) or high-fat diet (HFD) for 8 weeks, respectively. Then the obese mice fed with HFD were randomly allocated into 3 sub-groups: the HFD group (n = 10); the HFD + CUMS group (n = 10); the HFD + CUMS + L.r group (n = 10). The latter 2 subgroups underwent CUMS for 4 weeks to build the obesity and depression comorbidity mice model. During the duration of treatment, mice were gavaged with 0.5 mL PBS solution or L. reuteri (2 × 109 CFU/mL) once a day, respectively. The body weight, food intake, organ weight, behavioral indicators, histology, blood lipids, levels of inflammatory cytokines and tight junction proteins and abundance of colonic contents bacteria were measured.Results: The obesity and depression comorbidity mice model was successfully established after HFD feeding and chronic stress. The comorbid mice demonstrated inflammatory responses increase in liver and adipose tissues, worsened damage to the intestinal barrier as well as gut microbiota disorder. Gavaged with L. reuteri attenuated depressive-like behavior, improved blood lipids and insulin resistance, reduced inflammation in liver and adipose tissues, improved intestinal tight junctions as well as the microbiome dysbiosis in obesity and depression comorbidity mice.Conclusion:Lactobacillus reuteri strain 8008 could alleviate depressive-like behaviors and related indicators of obesity disorders by regulating the gut microbiota in obesity and depression comorbid mice.